2007
DOI: 10.1177/0969733007075865
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Moral Judgment Between Nursing Students and Qualified Nurses

Abstract: This longitudinal study examined how nursing students' moral judgment changes after they become qualified nurses working in a hospital environment. The sample used was a group of 80 nursing students attending a university in Suwon, Korea, between 2001 and 2003. By using a Korean version of the Judgment About Nursing Decisions questionnaire, an instrument used in nursing care research, moral judgment scores based on Ketefian's six nursing dilemmas were determined. The results were as follows: (1) the qualified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 14 publications
1
13
0
4
Order By: Relevance
“…It was concluded that activities that help nurses understand and use principled moral judgements should facilitate their confidence in their clinical decision‐making. Furthermore, qualified nurses were found to have significantly higher moral judgement scores than nursing students (Kim, Park & Han 2007). Kim et al .…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that activities that help nurses understand and use principled moral judgements should facilitate their confidence in their clinical decision‐making. Furthermore, qualified nurses were found to have significantly higher moral judgement scores than nursing students (Kim, Park & Han 2007). Kim et al .…”
Section: Discussionmentioning
confidence: 99%
“…We sent three questionnaires to one university and requested that they be distributed to three faculty members who were responsible for leading clinical practice (one of whom was involved in the field of fundamental nursing). In the field of fundamental nursing, the faculty members are often responsible for conducting courses on nursing ethics, and previous studies have shown that student nurses often experience ethical problems in clinical practice [14]. …”
Section: Methodsmentioning
confidence: 99%
“…Issues such as not telling patients the truth [12] and the inappropriate provision of information [13] were also indicated as ethical problems. Student nurses who were the subjects of these investigations were typically at least third-year students; however, these students reportedly also experienced various ethical problems during fundamental clinical practice [14]. The results of one study regarding the experience of student nurses during clinical practice revealed that the nursing faculty offered very little support [7].…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars are keen to stress the distance between the 'ideal' ethical choice and the 'real' ethical behaviour (Raines, 2000;Kim et al, 2007). Some studies illustrate how nurses have difficulties to implement their decisions in practice underlining the importance of contextual factors in limiting the ability of nurses to put into practice their decisions or to act according to their values (Dierckc de Casterlé et al, 1997Raines, 2000;Rodney et al, 2002;Varcoe et al, 2004;Kim et al, 2007).…”
Section: Emotional Warmth and Perception Of Ethical Problemsmentioning
confidence: 99%